PENGARUH APLIKASI TOPIKAL GEL EKSTRAK DAUN JAMBU BIJI (Psidium guajava Linn.) TERHADAP JUMLAH SEL MAKROFAG PADA PROSES PENYEMBUHAN LUKA GINGIVA LABIAL (Kajian in-vivo pada Sprague dawley) - , MAHADNA AULIA RAHMAH, drg. Sri Pramestri L., M.S., Sp.Perio(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gingiva is a part of oral mucosa which injury often occured. Macrophages is inflammatory cells which function to phagocytes and produce important cytokines. Guava leaves (Psidium guajava Linn.) contains flavonoids that can accelerate the wound healing process. The aim of this study was to determine the effect of topical application g uava leafâs (Psidium guajava Linn.) extract gel on the number of macrophages in the wound healing process of gingival (in-vivo studies on Sprague dawley). Twenty seven male Sprague dawley were divided into three groups, each 9 rats in treatment group (Psidium guajava leaf extract gel), positive control group (Aloclairâ¢ gel), and negative con trol group (CMC-Na 2%). Each rats were given injury at the lower centralis incisor labial gingival using a 2,5 mm diameter of punch biopsy. Topical application given to each group for 7 days with frequency of 2 times a day, after that the ratâs injur y tissue w ere decapitated to made histological samples using Hematoxylin Eosin staining. Number of macrophages in wound area was counted under a light microscope 400 times magnification in 6 fields of view. The result of this research on day-3, 5 and 7 showed that was a significant differences in the number of macrophage between guava leaf extract gel groups, and Alocla irâ¢ gel groups with CMC-Na groups, meanwhile there were no significant differences between g uava leaf extract gel and A locla irâ¢ gel. The conclusion of this research was the application of guava leaves (Psidium guajava Linn.) extract gel can reduce the number of macrophages in the wound healing process of gingival (in-vivo studies on Sprague dawley). Keywords : Psidium guajava Linn., Wound Healing, Macrophage